Analisis Risiko Paparan Karbon Monoksida (CO) Terhadap Pedagang Pasar Tradisional Kota Jambi - Anggelina, Yossi Kristin; Amalia , Nurul; Febri Juita Anggraini; Zuli Rodhiyah (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
Vehicles are one of the most common of transportation used by people in their daily life. These vehicles produce emissions. One of the emissions released by vehicles is carbon monoxide (CO). carbon monoxide can cause chronic poisoning. This study aims to determine the concentration of CO and the risk of CO exposure to Traders at Traditional Markets in Jambi City. Measurements of CO concentrations were carried out in the two largest traditional markets in Jambi City, namely the Pasar Angso Duo Baru and the Pasar Rakyat Talang Banjar. Measurement of CO concentration using a CO meter for 6 days during busy market hours. Data collection for risk analysis was carried out by purposive sampling technique using a questionnaire. Respondent data obtained will be processed using Environmental Health Risk Analysis (ARKL). The results of the CO measurement in the Angso Duo Baru Market ranged from 3816,93 g/m3 – 23905,93 g/m3 and in the Pasar Rakyat Talang Banjar it ranged from 4867,08 g/m3– 21663,26 g/m3. The risk quotient value for 48 respondents in the Angso Duo Baru were >1. The results of RQ value calculation showed that 48 respondents at risk posed by CO. Risk Quotient for 29 respondents in the Pasar Rakyat Talang Banjar were >1. The results of RQ value calculation showed that 29 respondents at risk posed by CO.